2011
DOI: 10.1161/circresaha.110.232223
|View full text |Cite
|
Sign up to set email alerts
|

Docking Protein Gab1 Is an Essential Component of Postnatal Angiogenesis After Ischemia via HGF/c-Met Signaling

Abstract: Rationale: Grb2-associated binder (Gab) docking proteins, consisting of Gab1, Gab2, and Gab3, have crucial roles in growth factor-dependent signaling. Various proangiogenic growth factors regulate angiogenesis and endothelial function. However, the roles of Gab proteins in angiogenesis remain elusive.Objective: To elucidate the role of Gab proteins in postnatal angiogenesis. Methods and Results: Endothelium-specific Gab1 knockout (Gab1ECKO) mice were viable and showed no obvious defects in vascular development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 42 publications
4
67
0
Order By: Relevance
“…The resulting Gab1ECKO mice display impaired angiogenesis and enhanced necrosis in a hindlimb ischemia (HLI) model because of reduced HGF/c-Met signaling. 5 This finding is in agreement with another report showing that Gab1 is involved in ischemic and VEGF-induced angiogenesis using the same strategy for endothelial deletion of Gab1. 6 A third study using the Gab1ECKO mouse model further confirmed the requirement of Gab1 for postnatal angiogenesis.…”
Section: Article P 2031supporting
confidence: 92%
See 2 more Smart Citations
“…The resulting Gab1ECKO mice display impaired angiogenesis and enhanced necrosis in a hindlimb ischemia (HLI) model because of reduced HGF/c-Met signaling. 5 This finding is in agreement with another report showing that Gab1 is involved in ischemic and VEGF-induced angiogenesis using the same strategy for endothelial deletion of Gab1. 6 A third study using the Gab1ECKO mouse model further confirmed the requirement of Gab1 for postnatal angiogenesis.…”
Section: Article P 2031supporting
confidence: 92%
“…This observation is in line with the established role of these transcription factors as antiinflammatory regulators in the vasculature, 10 and with a previous publication by the same group implicating Gab1 in HGF-mediated induction of KLF2. 5 The concept of enhanced vascular inflammation in the absence of endothelial Gab1 is further supported by the immunohistochemical analysis of the aortic tissue conducted in this study. 1 Double deficiency of Gab1 and ApoE in the angiotensin-II exposed endothelium increased both vascular cell adhesion molecule-1 (VCAM-1) expression and macrophage infiltration of aortic tissue, both involved in the initiation and progression of atherosclerosis.…”
Section: Article P 2031supporting
confidence: 59%
See 1 more Smart Citation
“…It has been reported that HGF/cMet signalling in endothelial cells is involved in tumour angiogenesis and growth [9][10][11] . In addition, it has been demonstrated that the mice lacking endothelial expression of the cMet-docking protein Gab1, which mediates HGF/cMet signalling, exhibit no apparent defects in developmental angiogenesis, but show impairment in postnatal angiogenesis after ischaemia 40 . These observations indicate that endothelial HGF/ cMet signalling actively regulates pathological but not developmental angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have demonstrated that endothelial-specific Gab1 deficiency in mice impairs ischemia-induced angiogenesis. [16][17][18] Moreover, in contrast to the defects in cardiac development observed in Gab1 − / − mice, cardiomyocyte-specific Gab1 conditional knockout (Gab1-cKO) mice generated with the Cre-LoxP system are viable and display normal cardiac morphology at birth. 19 Gab protein family has three members, Gab1, Gab2 and Gab3.…”
mentioning
confidence: 99%